2010
DOI: 10.1007/s00520-010-1042-3
|View full text |Cite
|
Sign up to set email alerts
|

Perception of healthcare providers versus patient reported incidence of chemotherapy-induced nausea and vomiting after the addition of NK-1 receptor antagonists

Abstract: Aprepitant allows for better control of CINV in HEC regimens with CDDP, and this control is accurately perceived by physicians and nurses. However, physicians and nurses overestimate the control of delayed CINV after HEC regimens without CDDP and after MEC. CINV is still an important target for improved therapeutic intervention and the healthcare providers must be aware of its actual incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 26 publications
3
32
0
Order By: Relevance
“…4 Health professionals often underestimate the incidence and prevalence of CINV. 5 Most gynecologic cancer types are treated with highly emetogenic chemotherapeutics, such as cisplatin, carboplatin, paclitaxel, and cyclophosphamide when paclitaxel is not available. 6 These drugs are reported to cause emesis in more than 90% of patients without prophylactic use of antiemetics 7 and may seriously impact QoL.…”
mentioning
confidence: 99%
“…4 Health professionals often underestimate the incidence and prevalence of CINV. 5 Most gynecologic cancer types are treated with highly emetogenic chemotherapeutics, such as cisplatin, carboplatin, paclitaxel, and cyclophosphamide when paclitaxel is not available. 6 These drugs are reported to cause emesis in more than 90% of patients without prophylactic use of antiemetics 7 and may seriously impact QoL.…”
mentioning
confidence: 99%
“…Since healthcare professionals tend to underestimate symptoms compared with patients [17,18], methods based on patient reports are more appropriate to accurately record the symptoms. Many tools based on patient reports have been shown to be effective in recording CINV symptoms, including the Morrow assessment of nausea and emesis (MANE) [24], Rhodes INRV [21], Osoba Nausea and Emesis Module based on the European Organization for Research and Treatment of Cancer (EORTE) QLQ-C30 [25], CINE QOL questionnaire by Martin et al [26], and Functional Living Index-Emesis (FLIE) with a focus on QOL [27].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, however, a daily patient diary is seldom used because of the burden on the patients who fill it in and the healthcare professionals who analyze and assess the results. In outpatients receiving cancer chemotherapy in particular, physicians often assess symptoms observed during consultations alone, generating a gap between symptoms assessed by healthcare professionals and those really experienced by patients [17,18], and thus precluding appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The recent re-classification of the AC regimen from being moderately-emetogenic to highly-emetogenic by the American Society of Clinical Oncology [34] suggests the need to improve the use of NK1-RAs, such as aprepitant, in CINV control. Furthermore, it was found that clinicians tend to underestimate the incidences of nausea [34], as well as overestimate the control of delayed CINV in patients on MECs and HECs without cisplatin [35]. As such, there is also imperative need for more research to be done in this area.…”
Section: Cinv Control With Nk1-ras-are Wementioning
confidence: 99%